Activation by Glutathione in Hypoxic Environment of an Azo‐based Rhodamine Activatable Photosensitizer. A Computational Elucidation. Issue 13 (9th February 2022) - Ponte, Fortuna; Mazzone, Gloria; Russo, Nino; Sicilia, Emilia
Abstract: In the present paper, density functional theory (DFT) has been applied to the study of the activation mechanism of a new selenium azo‐rhodamine (azoSeRho) in presence of the tripeptide thiol, glutathione (GSH), as potent activatable photosensitizer to be employed in photodynamic therapy. The introduction of the azo group into the conjugated system of the seleno‐rhodamine dye and its reaction with GSH allow the selective formation of the active photosensitizer, SeRho. Furthermore, DFT calculations have allowed to shed light on the activation mechanism of the azoSeRho photosensitizer when molecular oxygen is present and hydrogen peroxide is formed. This study is the first theoretical investigation revealing how the reductive cleavage of the azo moiety by GSH occurs. Time‐dependent DFT approach has been used to evaluate the chalcogen‐substitution effect on the structures and photophysical properties of the azo derivatives and, then, on the activated photosensitizers. Abstract : Mediated reduction : The mechanism of glutathione (GHS)‐mediated reduction of the activatable photosensitizer azoSeRho to the active drug SeRho has been computationally elucidated and requires four GSH molecules to take place. The SeRho formation is favoured in hypoxic environment. The exploration of the SeRho photophysical properties have allowed to highlight its intrinsic properties that make is suitable to trigger type II photoreactions in photodynamic therapy.